Analisis Problematika Pendidikan Indonesia Di Wilayah 3T - Ayudhia Nur Luthfia; Nabila Putri Wahiddiyah; Desy Safitri; Sujarwo Sujarwo (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The education system in Indonesia is regulated by Law of the Republic of Indonesia Number 20 of 2003. The constitution contains the meaning, purpose and matters relating to education in Indonesia. However, if we look further, the implementation of education in Indonesia is still far from what is stated in the constitution of Law No 20 of 2003. Efforts are needed to improve the quality of education of Indonesia's young generation, especially in the 3T areas, as well as providing education services, overcoming teacher limitations, and equalizing education in the 3T areas throughout Indonesia. To be able to develop education policies and solutions in Indonesia, we need to analyze the problems of education in Indonesia..